Risk Factor About Stunting Among Toddlers Aged 24-59 Months in Sabang City - Ramadhaniah Ramadhaniah; Adityo Sendi; Azwar Eddy; Teuku Muliadi (Universitas Teuku Umar, 2021)
Stunting is a difficult problem faced by all countries today. Data shows that in 2017 the stunting rate reached 22.2%, or about 150.8 million toddlers experienced stunting. In this study, we used a crossectional research design with a total sample of 1489 people. Our results showed 61.9% of toddlers suffered from stunting, 69.8% of respondents with good health care patterns, 74.6% of respondents who had a history of infectious diseases in the existing category, 58.7% of respondents with NLHB in the poor category, and 74.6%. The category of respondents to the information media that ever existed. those at risk of stunting are health patterns (p-value = 0.017), history of infectious diseases (value p = 0.020) and NLHB (value p = 0.031).